Is prioritisation of funding in elite sport effective? An analysis of the investment strategies in 16 countries - de Bosscher, V.; Shibli, S.; Weber, A. C. (European Sport Management Quarterly, 2019)
Research question: This paper explores the extent to which nations prioritise elite sport funding; whether such nations are more successful than those whose funding is more diversified; and, if the sports that receive the most funding are also the most successful.